2002
DOI: 10.1021/ja026699l
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Two Different Active Oxygen Species in Cytochrome P450 BM3 Mediated Sulfoxidation and N-Dealkylation Reactions

Abstract: Herein, we report the results from two experiments that are consistent with sulfoxidation and N-dealkylation involving two different enzyme substrate complexes and thus two different active oxygen species that do not interchange. The first experiment involves the use of a mutant that may increase the amount of the hydroperoxy-iron species (FeIIIO2H).1 This mutant increases the amount of sulfoxidation relative to the amount of N-dealkylation by 4-fold. In a second experiment, deuterium substitution on the N-met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
124
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(134 citation statements)
references
References 23 publications
9
124
0
1
Order By: Relevance
“…Thus, for both the reactions to occur from both oxidants, it is required that the relative energy of formation of 3 and 4 be identical for both oxidizing species. In fact, mutants that purportedly enhance Cpd 0 have been shown to alter product ratios and rates of reaction in every case, indicating a difference in the energetics of the two oxidants Vatsis and Coon, 2002;Volz et al, 2002;Jin et al, 2003;Chandrasena et al, 2004) and consistent with computational results (Ogliaro et al, 2002).…”
Section: Single Oxidant For P450supporting
confidence: 70%
See 2 more Smart Citations
“…Thus, for both the reactions to occur from both oxidants, it is required that the relative energy of formation of 3 and 4 be identical for both oxidizing species. In fact, mutants that purportedly enhance Cpd 0 have been shown to alter product ratios and rates of reaction in every case, indicating a difference in the energetics of the two oxidants Vatsis and Coon, 2002;Volz et al, 2002;Jin et al, 2003;Chandrasena et al, 2004) and consistent with computational results (Ogliaro et al, 2002).…”
Section: Single Oxidant For P450supporting
confidence: 70%
“…In separate studies, Hutzler et al (2003) have suggested that two different oxidants may be involved in O-dealkylation and N-dealkylation. Jin et al (2003) came to the conclusion that Cpd 0 could epoxidize alkenes but not hydroxylate the high-energy aliphatic C-H bond on camphor, and Volz et al (2002) suggested that Cpds 0 and 1 may be the sole oxidants involved in N-dealkylation and sulfoxidation, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The enzymes catalyze a broad range of reactions such as hydroxylation [5], decarboxylation [6], epoxidation [7], reductive dehalogenation [8], amine/oxygen dealkylation [9], and sulfoxidation [10], employing molecular oxygen and electrons [e.g. from NAD(P)H].…”
Section: Introductionmentioning
confidence: 99%
“…[8] Studies of the kinetics of wildtype and mutant P450 BM3 catalyzed oxidation of a subtrate with both amine or thioether moieties led to the postulate that two separate oxidants affect amine and thioether oxidation; the oxidation of sulfur was greater for the mutant in which Cpd 0 activity is potentiated. [8] An alternative explanation of these results that does not implicate Cpd 0 was proposed in which different spin states of Cpd I masquerade as two different oxidants. [3] Whether Cpd 0 does play a role in wildtype P450 catalyzed sulfoxidation was thus unclear.…”
mentioning
confidence: 99%